STUDI KASUS: ASUHAN KEPERAWATAN KELUARGA DENGAN ANAK REMAJA DALAM PENCEGAHAN PERILAKU MEROKOK - La Syam Abidin (Jurnal Keperawatan Indonesia Timur (East Indonesian Nursing Journal), 2021)
Background: Adolescence allows the involvement of health risk behaviors, including smoking. Adolescents need family support, especially in prevention and treatment. Nurses can help families through nursing care. Objective: To describe the application of family nursing care with adolescent children to prevent smoking. Methods: The population is a family with teenagers. The sampling technique used purposive sampling. The sample is the family of Mr. S. with inclusion criteria; Nuclear family, stage of family development in adolescence, early teens aged 10-18 years, smoking history of family members, family members can read and write and are willing to be respondents. They were collecting data through interviews, observation, and documentation studies. The research instrument was the researcher himself, family nursing care, and nursing kit equipment format. Results: The study found three nursing problems. Nursing diagnoses include deficiencies in family knowledge, risky health behaviors, and ineffective family health care. Planning adjusted the diagnosis found, the intervention goals for four weeks, the outcome criteria using the Nursing Outcome Classification, and the intervention using the Nursing Intervention Classification by adjusting the five family health tasks. Implementation includes health screening, health education, counseling, youth social skills. The evaluation shows success in overcoming family nursing problems. Conclusion: The application of family nursing care increases family involvement in preventing adolescent smoking behavior.